Empirical Study: Entrepreneurs Performance of Micro, Small and Medium Enterprises (MSMEs) in Tanjung Morawa A Village, Deli Serdang, North Sumatra, Indonesia - Riana, Rida; Syamsuri, Abd. Rasyid (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2022)
This study intends to examine how social capital, inventiveness, and product innovation impact the entrepreneurs performance of Micro, Small, and Medium-Sized Enterprises (MSMEs) in Tanjung Morawa A Village, Deli Serdang, North Sumatra, Indonseia. This study used a quantitative research design. The period of time for doing this research is from March to May 2022. Observation, study documentation, and questionnaires are the data collection methods used. Up to 65 UMKM offenders from Tanjung Morawa A Village make up the study's population. A quota sampling method was used to sample each population. Multiple linear regression using the SPSS program is the analysis strategy used in this study. The study's findings demonstrate that social capital has a positive and significant impact on MSME players' performance. The performance of MSME actors is positively and significantly impacted by creativity. Product innovation positively and significantly impacts how MSME actors operate. Overall, the performance of MSME actors is positively and significantly impacted by social capital, creativity, and product innovation. This study's coefficient of determination (R2) is 0.700, which suggests that social capital, creativity, and product innovation may account for 70% of the success of MSME actors.